Evaluation of a short-term ultrasound curriculum on promoting interest in healthcare and sciences for deaf and hard of hearing students. Issue 1 (24th November 2020) - Fischetti, Chanel; Nguyen, Thalia; Bashir, Rame; Whited, Matthew; Mazumder, Proma; Saadat, Soheil; Moeller, John; Lahham, Shadi; Fox, John C.
Abstract : Purpose: The objective of this study was to determine if exposure to a short-term ultrasound basic biology and anatomy course can promote interest in health careers and other science-related endeavors among DHH students. Design/methodology/approach: This was a single-site, prospective observational study of DHH high school students at a Southern California high school. All participants took a pre-test survey prior to the course. Participants then took part in three teaching sessions which taught basic anatomy using point-of-care ultrasound (POCUS). Following instruction, a post-test survey was performed to determine if students had an increased interest in medicine, science and biology ( p = 0.151). Findings: 28 students were enrolled in the study, with an equal distribution of boys and girls. Initially, subjects reported their interest in medicine at an average of 2.8 ± 1.10. The reported interest in science was 3.0 ± 1.13 and for biology was 3.0 ± 1.19. The change in participants' interest was not statistically significant for medicine ( p = 0.791), science ( p = 0.225) and biology. Practical implications: While our data did not demonstrate a statistically significant difference in students' interest in STEM fields after the training course, there were several students who were interested in more hands-on shadow experience after the course. Regardless, this study demonstrates persistent barriers that exist for a person who is deaf or hard of hearing to engage in the STEM fields. Future studies are needed to determine the level of instructional activities that may impact the careers of these students. Originality/value: Point of care ultrasound has been shown to be an effective teaching modality in medical education. However, to date, no studies have been done to assess the utility of ultrasound in teaching the Deaf and Hard of Hearing (DHH) population.